Synthesis and characterization of novel, low cost and earth abundant iron based magnetocaloric materials - Ye, Qijun (2016)
Magnetocaloric materials that display good magnetocaloric effect at room temperatures are of high interest for the application of magnetic cooling technology. Current magnetocaloric materials that are suitable for room temperature applications usually contain rare earth metals such as Gadolinium, which are costly. To better enable magnetic cooling technologies to be used commercially, there is great interest in researching magnetocaloric effect of alloys that consist of cheaper and abundant materials. This project investigates the effect of Mn content in Fe (75 - x) Mnx Al25 alloy on its magnetic properties. 5 samples are prepared for x = 10, 12.5, 15, 17.5 and 25. The alloy is synthesized by the Mini-Arc Melter. The structural properties of the alloy, such as lattice parameter, Miller indices, strain and structure, are characterised by the X-ray Diffraction (XRD) while the magnetic properties of the alloy is characterised by the Vibrating Sample Magnetometer (VSM). The elemental composition of the alloy is checked using the Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM/EDX). The samples has a face centered cubic structure with Fm3m space group and ordered L21 structure. The field dependent magnetization curves Fe (75 – x) Mnx Al25 show that the samples are soft. The Curie temperature of 2 samples, x = 15 and 17.5, are close to room temperature. The MCE properties for x =15 and x = 17.5 were calculated and the -∆Sm values are 0.97 and 1.01 J/kg K, and have relatively high RCP values (418 and 380 J/kg respectively). In conclusion, the composition of Fe (75 – x) Mnx Al25 at x = 15 has the best magnetocaloric properties among the samples. It exhibit soft magnetic properties with low hysteresis loss, TC near room temperature and high RCP value that is greater even than the benchmark magnetocaloric material, Gadolinium. Using other methods of synthesizing, such as melt spinning and high energy ball milling can further optimize the saturation magnetization while maintaining its soft magnetic properties.